2024
DOI: 10.1038/s41598-024-54754-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of human papillomavirus infection and associated factors among women attending cervical cancer screening in setting of Addis Ababa, Ethiopia

Elsa Tesfaye,
Birhanu Kumbi,
Belayihun Mandefro
et al.

Abstract: Human papillomaviruses (HPVs) are circular, nonenveloped small double-stranded DNA viruses that infect stratified epithelium and can cause a number of life-threatening diseases. HPV is the central risk factor for developing cervical cancer and is estimated that approximately 98% of this disease is associated with oncogenic types of HPV. HPV infection leads to an estimated 266,000 cervical cancer deaths annually. Therefore, the objective of this study was to determine the prevalence of HPV infection and risk fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Several studies have revealed a notable prevalence of precancerous and cancerous cervical lesions (PCCL) in developing countries like Ethiopia, highlighting the significance of cervical cancer and HIV infection as major health concerns for women [ 2 , 3 , 19 ]. The objective of this particular study was to examine the occurrence and risk factors associated with PCCL among HIV-infected women at the University of Gondar Specialized Comprehensive Referral Hospital in Northwest Ethiopia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have revealed a notable prevalence of precancerous and cancerous cervical lesions (PCCL) in developing countries like Ethiopia, highlighting the significance of cervical cancer and HIV infection as major health concerns for women [ 2 , 3 , 19 ]. The objective of this particular study was to examine the occurrence and risk factors associated with PCCL among HIV-infected women at the University of Gondar Specialized Comprehensive Referral Hospital in Northwest Ethiopia.…”
Section: Discussionmentioning
confidence: 99%
“…The overall burden of cervical cancer is expected to increase further. Cervical cancer is the third most common cancer among women globally, with a range of 2.4 to 25.2%, and the second most common cancer in Africa, with a rate of 25.2% [ 3 – 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations